Flying under the radar: The effects of short-sale disclosure rules on investor behavior and stock prices - Stephan Jank; Christoph Roling; Esad Smajlbegovic (Deutsche Bundesbank, 2016)
This paper analyzes how newly introduced transparency requirements for short positions affect investors' behavior and security prices. Employing a unique data set, which contains both public positions above and confidential positions below the regulatory disclosure threshold, we offer several novel insights. Positions accumulate just below the threshold, indicating that a sizable fraction of short sellers are reluctant to disclose their positions publicly. Furthermore, we provide evidence that the transparency measures effectively represent a short-sale constraint for secretive investors, which results in stocks to be overpriced. Specifically, when this constraint is potentially binding, stocks subsequently exhibit a negative abnormal return of 1.0-1.4% on a monthly basis. Different placebo tests verify that the short-sale constraint originates from the disclosure threshold. Overall, these findings suggest that short sellers' evasive behavior in response to the transparency regulation imposes a negative externality on stock market efficiency.
Keywords: G14; G15; G23; 330; short selling; transparency; investor behavior; stock market efficiency